Euthanasia phenomenon: ethical, medical and legal aspects (Journal of actual problems of jurisprudence, 2020)
Since ancient times, social consciousness excited by the phenomenon of euthanasia. In the modernperiod, the ethical, medical and legal problems of euthanasia are topical issues. Euthanasia is one of themain sections of thanatology – teachings about death. The main issue under discussions, is the questionof legalizing euthanasia in the legislation of modern states. The purpose of the article is to analyze thecurrent situation of this problem from the ethics, medicine and law points of view. The research appliedmodern scientific methods. A wide range of foreign sources and legislative acts of different countries isanalyzed. A global debate on the expediency of legalizing euthanasia has been analyzed. The applicationof general scientific methods allowed us to compare the domestic and international methodologyof work. The classifying of states based on the criterion of legalization or prohibition of euthanasia wasconducted. The examples of the legal framework for the use of euthanasia in the Netherlands, Belgium,and the USA examine the problem of legal regulation of the euthanasia procedure. The problem of legalregulation of euthanasia is considered in conjunction with ethical and medical issues.As a result of the study, the conclusions were reached. The article identifies possible consequencesfor the medical ethics, taking into account the legalization of euthanasia in a growing number of countries.Particularly the assumption of how medical codes of ethics should adapt to the current state of theproblem is grounded.Key words: rights, euthanasia, death, medical ethics, law, legalization, prohibition.